Primiparous and multiparous Friesland, Jersey, and crossbred cows’ behavior around parturition time at the pasture-based system in South Africa - Zuko, Mpisana; Jaja, Ishmael Festus (Journal of Advanced Veterinary and Animal Research, 2020)
Objective: The objective of the study was to assess the behavioral attributes of primiparous and multiparous Friesland, Jersey, and Crossbred cows around calving time in a pasture-based dairy system. Material and methods: A total of 120 pregnant cows were used in the study, comprising of 40 cows per genotype in different parities [A-primiparous (n = 10), B-2 to 4 (n = 10), C-5 and 6 (n = 10), and D-7 and 8 (n = 10)] and kept in a maternity paddock. Five observers monitored cows from the onset of parturition until the calves were fully expelled, recording the frequency and duration of lying, standing, and walking bouts, calf licking, and suckling. Results: There were differences (p < 0.05) observed in the behavioral patterns around the time of calving. Jersey multiparous cows spent (p < 0.05) significantly most of their time (20.50 ± 3.10) in lying position as compared to the other genotypes. The Jersey cows also spent most (p < 0.05) of their time (48.00 ± 0.34) in a standing position during the calving period. Friesland cows spent (p < 0.05) most of their time (12.00 ± 1.19) exhibiting either stepping or walking attributes as compared to Jersey and Crossbred cows. The Jersey genotype spent significantly (p < 0.05) more time (123.00 ± 10.43) in expelling their calves compared to the other genotypes. There was a significant (p < 0.05) interaction between genotypes and parity on time spent by cows on licking their calves. There was a significant difference (p < 0.05) observed between the genotypes of the primiparous cow. Conclusion: The primiparous cows spent most of their time in standing and the least amount of time in other activities throughout the trial due to the lack of maternal experience. The current study revealed that behavioral activities differ according to genotype and parity. Adv. Vet. Anim. Res., 7(2): 290-298, June 2020